Glacioeustasy, meteoric diagenesis, and the carbon cycle during the Middle Carboniferous. (14th October 2015) - Dyer, Blake; Maloof, Adam C.; Higgins, John A.
Abstract: Middle Carboniferous carbonates in the western U.S. have undergone Pleistocene Bahamas‐style meteoric diagenesis that may be associated with expanding late Paleozoic ice sheets. Fourteen stratigraphic sections from carbonate platforms illustrate the regional distribution and variable intensity of physical and chemical diagenesis just below the Middle Carboniferous unconformity. These sections contain top‐negative carbon isotope excursions that terminate in regional exposure surfaces that are associated with some combination of karst towers, desiccation cracks, fabric destructive recrystallization, or extensive root systems. The timing of the diagenesis is synchronous with similarly scaled top‐negative carbon isotope excursions observed by others in England, Kazakhstan, and China. The mass flux of negative carbon required to generate similar isotopic profiles across the areal extent of Middle Carboniferous platform carbonates is a significant component of the global carbon cycle. We present a simple carbon box model to illustrate that the δ 13 C of dissolved inorganic carbon in the ocean could be elevated by ∼1.4 ‰ as isotopically light carbon from the weathering of terrestrial organic matter reacts with exposed platforms before reaching the ocean and atmosphere. These results represent an improvement on global biogeochemical models that have struggled to provide a congruent solution to the high δ 13 C of the late Paleozoic icehouse. Key Points: Meteoric diagenesis in the mid‐Carboniferous is a global phenomenon Meteoric diagenesis of carbonates can increase the δ 13 C of the ocean This increase in ocean δ 13 C is decoupled from organic carbon burial